PENGARUH TEPID SPONGE DALAM MENURUNKAN SUHU TUBUH ANAK USIA PRA SEKOLAH YANG MENGALAMI DEMAM DI RUMAH SAKIT TENTARA BHAKTI WIRA TAMTAMA SEMARANG: THE EFFECT OF TEPID SPONGE IN REMOVING THE BODY TEMPERATURE OF PRE-SCHOOL AGE CHILDREN WHO HAVE FEVER AT THE BHAKTI WIRA TAMTAMA ARMY HOSPITAL, SEMARANG - Suprapti E; Rahmanti A; Liban A.M (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2020)
Fever itself is a condition in which the body temperature is experiencing an increase in heat above the normal temperature. Fever can be treated pharmacologically and non-pharmacologically in various ways, one of which is by using water tepid sponge therapy. This study aims to determine the effectiveness of giving water tepid sponge to pre-school age children who have fever at the Bhakti Wira Tamtama Army Hospital Semarang. The design of this study used Quasy experimental pre-post test equivalent control group. The number of samples is 20 respondents with the total sampling method. The results showed that there was an effect of water tepid sponge on decreasing body temperature in children aged 36-60 months who had fever with p value 0.000, an average decrease of 1.50C. The recommendation of this study is that the provision of a water tepid sponge can be used as an independent nursing intervention in reducing the body temperature of preschool-aged children who have fever.